2023
DOI: 10.21511/ppm.21(2-si).2023.02
|View full text |Cite
|
Sign up to set email alerts
|

University without Walls: Experience of Berdyansk State Pedagogical University during the war

Abstract: This study presents the experience of managing Berdyansk State Pedagogical University in the first year of a full-scale war. The purpose is to analyze the impact of management decisions on the performance indicators of the university in the conditions of temporary occupation and relocation to a new place. The relocation of Berdyansk State Pedagogical University (BSPU) to a safer territory enabled the resumption of educational activities in May 2022, after 53 days of functioning under occupation by russian troo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…The almost equivalent number of publications in the pre-war and wartime periods is related to the fact that even during the war, faculty members understood their responsibility to society. Additionally, the university introduced free publications in a professional journal, which encouraged faculty members to submit their articles for publication (Lopatina et al, 2023) At the same time, the responses from the respondents to the question "Indicate which period was the most successful for your publishing activity over the past 5 years?" (Figure 1) showed that for a larger number of faculty members, 46.2% of the most successful periods were before COVID-19 and the war in Ukraine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The almost equivalent number of publications in the pre-war and wartime periods is related to the fact that even during the war, faculty members understood their responsibility to society. Additionally, the university introduced free publications in a professional journal, which encouraged faculty members to submit their articles for publication (Lopatina et al, 2023) At the same time, the responses from the respondents to the question "Indicate which period was the most successful for your publishing activity over the past 5 years?" (Figure 1) showed that for a larger number of faculty members, 46.2% of the most successful periods were before COVID-19 and the war in Ukraine.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, over the past five years, the world has undergone various dynamic changes that have impacted the effectiveness of teachers. These changes include COVID-19 (Gewin, 2021;Naumann et al, 2022;Pyhältö et al, 2023), Russia's war against Ukraine (Kurapov et al, 2023;Lopatina et al, 2023;Suchikova, 2023;, and a constant transformation of Ukraine's educational policy, which affects the list of faculty members' duties and scientific activity, ultimately impacting their effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The need to develop digital competencies is also mentioned in other studies (Barbas and Matos, 2023; Brown, 2023). These issues are especially relevant today for Ukraine, where most universities operate online in a distance format (Lopatina et al, 2023; Marynchenko et al, 2022; Suchikova, 2023; Suchikova et al, 2023; Suchikova and Tsybuliak, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a significant number of academic staff members have been forced to flee their homes due to the occupation of their hometowns or escalating military activities. As a result, they have sought refuge in safer regions of Ukraine or abroad, causing additional personal tribulations and stress 34 , 42 . Some members of academic staff have been, or continue to be, subjected to relentless attacks by occupiers while residing in occupied territories 43 , 44 .…”
Section: Introductionmentioning
confidence: 99%